Quality of Service guarantees and fault-tolerant TCP services in mobile wireless optical networks. (21st May 2008) - Cardei, Ionut; Pavan, Allalaghatta; Bettati, Riccardo
In this paper we address the problem for communications Quality of Service (QoS) in wireless networks of Mobile Optical Free-space networks. We propose an architecture for end-to-end statistical delay guarantees. A delay model using the concept of virtual traffic accommodates variations in link capacity variations as well as transient outages. The QoS architecture uses an admission control technique that limits link utilisation for real-time traffic flows in order to reduce queuing delay. Admission control uses a 2-phase commit protocol for handling QoS negotiation and adaptation. We also present a mechanism for deploying QoS-enabled dependable TCP services in this network. The primary-backup TCP replication mechanism is supported by the routing infrastructure and improves server deployment transparency compared to previous work. We illustrate application performance improvement with simulation results.